Waging the war within : a marine's memoir of Vietnam and PTSD - Fortner, Tim, 1948-; Ridley, Elizabeth (McFarland & Company, Inc., Publishers, 2020)
"U.S. Marine Sergeant Tim Fortner survived 14 months in Vietnam as a door gunner in a CH-46 helicopter, completing 27 strike flight missions. He was awarded the Air Medal for heroic achievement in aerial flight. Like many veterans, his real battle didn't begin until he returned home, where he struggled to adjust to the "new normal" of American life in 1969, still haunted by his experiences during the nation's most unpopular war. His memoir describes his military training, his unit's harrowing missions inserting and extracting troops over landing zones under enemy fire, and his four-decade struggle with service-connected PTSD"--